2022
DOI: 10.3390/nano12213804
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-Derived Porous Carbon with a Good Balance between High Specific Surface Area and Mesopore Volume for Supercapacitors

Abstract: Porous carbon has been one desirable electrode material for supercapacitors, but it is still a challenge to balance the appropriate mesopore volume and a high specific surface area (SSA). Herein, a good balance between a high SSA and mesopore volume in biomass-derived porous carbon is realized by precarbonization of wheat husk under air atmosphere via a chloride salt sealing technique and successive KOH activation. Due to the role of molten salt generating mesopores in the precarbonized product, which can furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Supercapacitors are widely renowned for their superior performance, broad operating temperature range, and high life expectancy, which makes them an ideal energy storage device. Supercapacitor performance is mainly influenced by electrode materials. Currently, various carbon materials have been developed for energy storage, including carbon nanotubes, , porous carbons, graphene, and carbon fibers. , Compared to other carbon materials, porous carbons are promising materials for electrodes in supercapacitors due to their high specific surface area (SSA), superior porosity, abundant precursors, and simple preparation process. Additionally, the performance of supercapacitors is determined by their SSA and pore size distribution. For instance, He et al prepared porous carbon with a large SSA (2208 m 2 g –1 ) and microporosity (more than 71.8%), but it is not beneficial to the fast transport of ions and results in a poor rate performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supercapacitors are widely renowned for their superior performance, broad operating temperature range, and high life expectancy, which makes them an ideal energy storage device. Supercapacitor performance is mainly influenced by electrode materials. Currently, various carbon materials have been developed for energy storage, including carbon nanotubes, , porous carbons, graphene, and carbon fibers. , Compared to other carbon materials, porous carbons are promising materials for electrodes in supercapacitors due to their high specific surface area (SSA), superior porosity, abundant precursors, and simple preparation process. Additionally, the performance of supercapacitors is determined by their SSA and pore size distribution. For instance, He et al prepared porous carbon with a large SSA (2208 m 2 g –1 ) and microporosity (more than 71.8%), but it is not beneficial to the fast transport of ions and results in a poor rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical porous carbons (HPCs) with high SSA and enriched meso/macroporous structure are of interest as they exhibit excellent electrochemical properties. , HPCs not only provide a large SSA to store energy, but they also allow short ion diffusion paths, which can greatly improve the capacitive and rate performance of supercapacitors. , Nowadays, various precursors (e.g., polymer, biomass, and resins) are generally used to produce HPCs with outstanding electrochemical performance. Unfortunately, the low carbon yield, poor electrical conductivity, and high cost of these carbon precursors greatly limit the practical application in supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, Wang et al proposed a salt sealing technology combined with potassium hydroxide activation to convert pre-carbonized wheat shells into high-performance carbon materials. This novel method could achieve a good balance between a high surface area and mesoporous volume of biomass-derived porous carbon due to the molten salt and the activation of potassium hydroxide, which provide both channels for fast ion transfer and abundant active sites for charge storage [5]. Thomas et al produced carbon particles from process lignin, sulfate lignin, soda lignin, lignin boost lignin and hydrolyzed lignin at different carbonization temperatures of 1000 • C and 1400 • C. It was found that the lignin source and carbonation temperature significantly affected the carbon quality and microstructure of carbon particles, which could in turn determine their performances in energy-storage devices [6].…”
mentioning
confidence: 99%